Research on bionic mechanism based endogenous security defense system - Aiqun HU; Lanting FANG; Tao LI (网络与信息安全学报)
Shell-based security defense technologies such as firewall, intrusion detection and anti-virus cannot be updated in a timely fashion upon identification of attacks.The security defense mechanism is not associated with the security status of network devices, resulting in low security performance.To solve the above problems, an endogenous security defense system based on the bionic security mechanism was proposed.Firstly, imitating the security defense mechanism of the organism, the endogenous security system integrated the security component with each other at the construction process.Secondly, the endogenous security associates all security components through network interconnection, and proposed a defense in depth and comprehensive approach to increase the security of a system.Finally, through the self-learning, endogenous security's ability of threat detection was continuous enhanced.By integrating the security system and information system, an endogenous security defense system was constructed.The endogenous security defense system can handle the challenges such as low defensive efficiency ratio, high-speed data processing, and unknown threats detection.The endogenous security system is an efficient security defense system of “innate growth and independent growth”.It meets the development needs of information systems with “high availability, security and high efficiency”.